2020
DOI: 10.1002/fsn3.1515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation and postcooking procedure on quality parameters and volatile compounds of beef jerky

Abstract: In this study, jerky samples were prepared from seasoned beef with and without the addition of starter culture. They were then dried or fried and analyzed to identify the quality parameters and volatile flavor compounds. Samples (starter and control) were divided into drying (inoculated-drying, I-D; noninoculated-drying, N-D) and frying (inoculated-frying, I-F; noninoculated-frying, N-F) groups. Water activity (a w ), lightness (L*), and redness (a*) values were significantly affected (p < .001) by the postcoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…These results are in accordance with those reported by Perea-Sanz et al [43]; however, they found that among this group of compounds (acetic acid and ethanol) were the most abundant compounds, whereas in the present study, the most abundant compound in the group of carbohydrate fermentation-derived volatiles was 2,3-Butanediol, [R-(R*,R*)]-. Similar to our findings, 2,3-butanediol was quantified as the dominant alcohol in Turkish sausages obtained from beef [46]. As reported by Luo et al [46], 2,3-Butanediol is formed by the reduction of methyl ketones from the α-oxidation of fatty acids and is often detected in fermented jerky.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in accordance with those reported by Perea-Sanz et al [43]; however, they found that among this group of compounds (acetic acid and ethanol) were the most abundant compounds, whereas in the present study, the most abundant compound in the group of carbohydrate fermentation-derived volatiles was 2,3-Butanediol, [R-(R*,R*)]-. Similar to our findings, 2,3-butanediol was quantified as the dominant alcohol in Turkish sausages obtained from beef [46]. As reported by Luo et al [46], 2,3-Butanediol is formed by the reduction of methyl ketones from the α-oxidation of fatty acids and is often detected in fermented jerky.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, 2,3-butanediol was quantified as the dominant alcohol in Turkish sausages obtained from beef [46]. As reported by Luo et al [46], 2,3-Butanediol is formed by the reduction of methyl ketones from the α-oxidation of fatty acids and is often detected in fermented jerky.…”
Section: Discussionsupporting
confidence: 91%
“…3c). (E)‐2‐octenal, tetradecanal, 1‐heptanol and (E)‐2‐decenal were also found in other fermented meat products, such as sausages and beef jerky (Corral et al ., 2016; Luo et al ., 2020). Nerol and linalool contributed to the sweet and citrus odour (Miyazawa et al ., 2016), while 1‐octen‐3‐ol and benzaldehyde conferred the mushroom, grassy and cherry‐marzipan odour (Giri et al ., 2010; Lv et al ., 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…e value, as the comprehensive value of meat color, is calculated by the following formula: e = a*/L + a*/b* [ 13 ]. The texture was measured using a mass structure instrument (TA-XTplus, Shanghai, China) following the method of Luo et al [ 14 ]. The thiobarbituric acid (TBARS, mg/100 g) and residue nitrite (mg/kg) were quantified according to the method of Ma, Nan, and Dai [ 15 ] and GB5009.33-2016 in China [ 16 ].…”
Section: Methodsmentioning
confidence: 99%